2013
DOI: 10.1371/journal.pone.0072813
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effects of Erythropoietin: A Focus on Behavioural and Hippocampal Processes

Abstract: Depression is a chronic and debilitating condition with a significant degree of relapse and treatment resistance that could stem, at least in part, from disturbances of neuroplasticity. This has led to an increased focus on treatment strategies that target brain derived neurotrophic factor (BDNF), synaptic plasticity and adult neurogenesis. In the current study we aimed to assess whether erythropoietin (EPO) would have antidepressant-like effects given its already established pro-trophic actions. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 73 publications
1
40
1
Order By: Relevance
“…EPO has the capacity to offer protection against a number of disease entities (208212) as well as enhanced biological activity (213, 214). For example, EPO has been reported to improve clinical outcome during development (215), neurodegenerative disorders (216), stroke (217222), aging (223), TBI (32, 224), vascular disease (217222), depression (208, 225), and metabolic disturbances (63, 211, 226, 227). …”
Section: Erythropoietin and The Modulation Of Mtormentioning
confidence: 99%
See 1 more Smart Citation
“…EPO has the capacity to offer protection against a number of disease entities (208212) as well as enhanced biological activity (213, 214). For example, EPO has been reported to improve clinical outcome during development (215), neurodegenerative disorders (216), stroke (217222), aging (223), TBI (32, 224), vascular disease (217222), depression (208, 225), and metabolic disturbances (63, 211, 226, 227). …”
Section: Erythropoietin and The Modulation Of Mtormentioning
confidence: 99%
“…For stem cell development and the maturation of cells, EPO relies upon mTOR for the differentiation of neural precursor cells to achieve a neuronal phenotype (254). EPO also has been shown to promote adult hippocampal neurogenesis that is considered to be important for effective antidepressant treatment and requires mTOR activity to resolve affective disorders (225). EPO also plays a role in osteoblastogenesis and osteoclastogenesis that is dependent upon pathways of mTOR (255).…”
Section: Erythropoietin and The Modulation Of Mtormentioning
confidence: 99%
“…Effects of exercise on brain functions and human studies have showed that insulin passes via the systemic circulation to the brain and it may have some physiologic actions which are different than its peripheral metabolic effects. Insulin resistance in peripheral tissues leads to the elevation of proinflammatory cytokines, neurotoxic ceramides, obesityinduced NADPH oxidase-associated oxidative stress in the brain, and insulin action on the brain is thought to be a regulator of peripheral glucose homeostasis in rodent studies via melatonin related mechanisms, increased unfolded protein response activation, mitochondrial and ER stress related overeating, leptin and insulin resistance, corticotropin-releasing factorrelated islet cell control [47,67,[99][100][101][102] . Recent studies of the mouse brain have demonstrated that degenerative plaque formation observed in AD (AD is the most prevalent form of dementia) is associated with insulin resistance [47,103] .…”
Section: Physiopathological Changes Caused By Dmmentioning
confidence: 99%
“…Moreover, they reported that Irisin not only mediates the animal's movements but also regulates adipose tissue thermogenesis by neurons in the caudal ventrolateral medulla and rostral ventrolateral medulla that are an integral component of the medullary sympathetic circuitry and these neurons project their axons to spinal sympathetic premotor neurons [198] . Similarly, it is known that resistance exercise improves body and brain bioenergetics for PD risk reduction [4] , insulin and leptin signaling in obese rats [2,45,82,104,199] , and exerts antidepressant-like effects via improving the impaired neuroplasticity [101,200] .…”
Section: Effects Of Exercise On the Brain Of Diabetic Animalsmentioning
confidence: 99%
“…Indeed, Epo and its receptors are found in the nervous system, including in neurons, astrocytes, and endothelial cells 16,18,22,23,25–27. Epo/Epo-R couple is involved in neuroprotection,28 promotes neural plasticity,29 and could have a potentially antidepressor effect 30,31. Furthermore, Epo/Epo-R pathway is required for normal brain development 32.…”
Section: Introductionmentioning
confidence: 99%